Privacy protection system and metrics for hiding electrical events. (13th April 2011) - Kalogridis, G.; Denic, S.Z.; Lewis, T.; Cepeda, R.
Smart grid privacy concerns the privacy of information extracted by analysing smart metering data. We present ElecPrivacy: a home electrical power management system that uses a rechargeable battery to mask home energy load signatures and, effectively, protect the privacy of appliance usage information. ElecPrivacy can be studied in the context of the classic communications problem, where input data is passed through a communication channel that distorts it. In this paper, we define and measure how the appearance of ElecPrivacy events can be estimated, or, reversely, how well the secrecy of this data is protected. In particular, we develop a range of privacy metrics by combining clustering, information theoretic (K-divergence), correlation and regression techniques, and testing over a large data set obtained from real home measurements.